Reforming of Marriage Law Through Constitutional Court Decision in Indonesia: Reformasi Undang-Undang Perkawinan Melalui Putusan Mahkamah Konstitusi di Indonesia - Rosa, Melia; Huda, Yasrul; Danil, Muhammad; Maulidah, Chabibatul; Arlis, Arlis (Jurnal Konstitusi, 2024)
The authority of the Constitutional Court to conduct judicial review against the 1945 Constitution often generates both support and criticism, particularly among those who feel disadvantaged by the existence of Law No. 1 of 1974. This study employs a qualitative research method with a normative juridical approach. The findings indicate that the Constitutional Court frequently engages in ijtihad (independent reasoning) when adjudicating cases. Additional considerations underlying these decisions include developments in science, technology, reform, and the renewal of Islamic thought, all of which influence the dynamic application of Islamic law in Indonesia. The implication of this study is that the Constitutional Court not only serves as an institution that tests statutory laws against the 1945 Constitution, but also plays an active role in legal interpretation (ijtihad), particularly concerning religious and matrimonial law. Consequently, the Court takes on a more prominent role in directing the development of Indonesian law in line with contemporary changes. Following the Court’s decisions, stricter oversight is necessary to ensure that legal amendments are effectively implemented in practice, so that the benefits of these reforms are truly felt by the public.